School Trips – Understanding the Young Traveller’s Perspective - Alina Zajadacz; Magdalena Kugiejko (Studia Periegetica, 2019)
The main purpose of the study was to collect and analyse opinions of young people concerning the organization of school trips, with special emphasis on factors that discourage them from participating in such trips. The research cycle was conducted in the years 2013-2017 using quantitative (survey) and qualitative (focus group interviews, participatory design) methods. The results provide interesting details about students’ participation in school trips (curriculum-based, extra-curricular), reasons for choosing not to attend school trips and students’ opinions (positive, negative) about school trips. It can be concluded that the inclusion of students’ opinions during the planning stage contributes to shaping their sense of empowerment and responsibility. The findings have not only a practical relevance for young people, teachers and providers of school trip services, but also wider social implications for the development of responsible and sustainable tourism.